Aid on the edge of chaos: rethinking international cooperation in a complex world - Ramalingam, Ben (Oxford University Press, 2013)
Aid has become a tangle of donors and recipients, so unwieldy that it is in danger of collapse. This ground-breaking book presents fresh thinking that transcends the 'more' verses 'less' arguments. Drawing on complexity theory it shows how aid could be transformed into a truly dynamic form of global cooperation fit for the twenty-first century.